2022
DOI: 10.1590/1678-4685-gmb-2021-0309
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the SARS-CoV-2 Gamma variant of concern (P.1): a perfect storm

Abstract: Our goal was to describe in more detail the evolutionary history of Gamma and two derived lineages (P.1.1 and P.1.2), which are part of the arms race that SARS-CoV-2 wages with its host. A total of 4,977 sequences of the Gamma strain of SARS-CoV-2 from Brazil were analyzed. We detected 194 sites under positive selection in 12 genes/ORFs: Spike, N, M, E, ORF1a, ORF1b, ORF3, ORF6, ORF7a, ORF7b, ORF8, and ORF10 . Some diagnostic sites for Gamma lacked a signature of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…This mutation plays a role in enhancing binding with ACE2 [29,30]. The Gamma variant contains mutations, such as N501Y, E484K, and K417T in the RBD [31]. Compar-ing the Alpha variant with Gamma, we found two more pockets for the Gamma variant, which could be attributed to the different number of mutations between the two variants.…”
Section: Discussionmentioning
confidence: 84%
“…This mutation plays a role in enhancing binding with ACE2 [29,30]. The Gamma variant contains mutations, such as N501Y, E484K, and K417T in the RBD [31]. Compar-ing the Alpha variant with Gamma, we found two more pockets for the Gamma variant, which could be attributed to the different number of mutations between the two variants.…”
Section: Discussionmentioning
confidence: 84%
“…Future therapies can target these regions of positive selection since they affect the fitness of the SARS-CoV-2 virus [44]. Previous studies have similarly observed positive selection in the SARS-CoV-2 spike protein open reading frame [44,45] and ORF1a [46,47]. SARS-CoV-2 ORF1a and ORF1b genomic RNAs are translated and cleaved into 16 NSPs [48] associated with viral genomic replication as well as suppression of host immune response and gene expression [49].…”
Section: Discussionmentioning
confidence: 96%
“…Compared with the sequence of the Beta mutant, in the S protein RBD of the Gamma mutant, lysine at position 417 is replaced with threonine (K417T), while the E484K and N501Y mutations are retained. In addition, there is an L18F mutation in the NTD, and threonine at position 20 is replaced by asparagine (T20N), proline at position 26 is replaced by serine (P26S), etc., ( Raman et al, 2021 ; Yépez et al, 2022 ). Therefore, for the ACE2 receptor, the Gamma variant has a binding affinity similar to that of the Beta variant, and mutation at these sites significantly reduces the neutralizing efficacy of monoclonal antibodies against the RBD and NTD.…”
Section: Sars-cov-2 Is Mutatingmentioning
confidence: 99%